The intergenerational transmission of Australian Indigenous languages: why language maintenance programmes should be family-focused - Forrest, Walter (My University, 2018)
By 2050, the majority of Australia’s surviving Indigenous languages are likely to become extinct. The intergenerational transmission of languages in which children acquire languages from their parents and grandparents is a key mechanism for reversing language shift, but many Australian children whose parents speak an Indigenous language do not speak that language. Using a unique, national survey of Australian Indigenous children, I identify factors associated with the successful intergenerational transmission of Indigenous languages within Aboriginal and Torres Strait Islander families. Results highlight the importance of parents’ language use. Although community-level characteristics account for some of the variance in successful language transmission, parents who use Indigenous languages at home, speak them as well as they speak English, and do not also speak a creole language are more likely to pass those languages onto their children.
Ethnic and Racial Studies
Keywords: Families and relationships; Intergenerational transfer